Transformative capacity to build an adaptive society resilience during crisis: evidence from conditional cash transfer/PKH Indonesia - Keukeu Komarawati; Muhammad Fadhil Nurdin; Wahju Gunawan; R. Nunung Nurwati (Frontiers in Sociology)
This research study the role of transformative capacity in building an adaptive society’s resilience to crises. This research focus on Indonesia’s Conditional Cash Transfer (CCT) program, Program Keluarga Harapan (PKH)/Family Hope Program in the COVID-19 pandemic, Cianjur. Social resilience emphasizes a return to pre-crisis conditions in the traditional view, but this research redefines resilience as the capacity to transform and adapt to new social condition. By analyzing PKH’s impact, this research show that this not only helped beneficiaries cope with crisis but also contributed to longterm changes that enhanced community resilience. This research using a qualitative approach, using interviews and direct observations of PKH beneficiaries in Cianjur. Data collection focuses on understanding the mechanisms through which PKH influenced individuals and families in their response to the crisis. The research examines how financial aid, together with program conditions related to health, education, and social welfare, contributed to behavioral and institutional transformations that strengthened resilience at the household and community levels. Research findings show that PKH played a significant role beside providing financial assistance. PKH also promotes long-term impact by improving access to healthcare, education, and social welfare services. PKH also contributed to changing beneficiaries’ perceptions on poverty and vulnerability, it increased community resilience in every opportunity. The research focus on how PKH facilitated institutional and behavioural transformations that strengthened community resilience during and beyond the pandemic. The study reinforce the importance of policies that support transformative resilience, and go beyond short-term relief to sustainable socioeconomic improvements. PKH’s role suggests that social protection programs should integrate elements that promote long-term resilience, ensuring that vulnerable communities are better equipped to face future crises. These findings offer valuable insights for policymakers in redefining adaptive social protection program and strategies.